There is an App for That: Mobile Technology Improves Complication Reporting and Resident Perception of Their Role in Patient Safety. Issue 1 (January 2021) - Johnson, Christopher R.; Noorzad, Ali; Pujari, Amit; Paiement, Guy; Lin, Carol
Abstract : Background: Morbidity and mortality (M&M) conferences are rooted within the culture of medicine. They serve a role in every training program and have been mandated by the Accreditation Council for Graduate Medical Education in surgical programs since 1983. Despite the patient safety improvements and educational benefits of these conferences, many adverse events are grossly under-reported. Methods: We developed a web-based, Health Insurance Portability and Accountability Act-compliant, M&M reporting mobile application based on Research Electronic Data Capture. The list of possible complications was based on the American Board of Orthopaedic Surgery complications list for part II. The interface is accessible through all mobile platforms. All residents were encouraged to use the application for real-time reporting of complications. Using an unpaired T-test, we compared the reporting before and after the implementation of the mobile application. Residents were surveyed using the Agency for Healthcare Research and Quality Patient Safety Culture Survey before and after implementation to evaluate resident perception of the department's culture of safety Results: The application was launched in August 2017. All reported events were tallied from August 2016 through July 2019. Before the implementation of the application, there were 54 adverse events reported, with a mean of 4.0 per month. In the Post-App cohort, a total of 176 adverse events were reported in year 1, with a mean of 14.76 per month, and 236 adverse events were reported in year 2, with a mean of 19.66 per month. Residents were significantly more likely to feel that their input on patient safety was valued by attendings after the implementation of the app (p = 0.0243). Conclusions: An anonymous mobile reporting method for M&M significantly increased the reporting of both major and minor complications and improved resident perception of their role in patient safety efforts. This suggests that traditional methods of M&M reporting may grossly underestimate the complication rates which can negatively affect patient safety and quality improvement efforts and that reducing barriers to the reporting of complication may improve resident engagement in patient safety.